Dynamics of Father attachment in Families with Children Experiencing Speech Delay - Ababilla, Haniffa; Hardew, Ayatullah Kutub (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
Speech Delay in Children Requires Complete Parent Attachment to Catch Up on Developmental Gaps. Many fathers have not yet understood the importance of this role, which can impact the child's social development, cognitive skills, abilities, and self-confidence. This research aims to explore father attachment dynamics in families with children experiencing speech delay. Using a qualitative phenomenological approach, the research involved four father participants with children aged 3-6 years experiencing speech delays. Data was collected through non-participant observation, semi-structured interviews, and documentation, then analyzed using Interpretative Phenomenological Analysis (IPA). The results revealed five primary themes: the complexity of speech delay, child development, paternal involvement, family support, and paternal deprivation. The research findings demonstrate that children with speech delays require comprehensive parent attachment. Father attachment is formed through consistent involvement that emphasizes interpersonal communication, openness, and speech stimulation in daily activities. Family support motivates fathers to build attachment by meeting the child's emotional needs. Conversely, paternal deprivation causes child alienation and delays in language development and other aspects. This research highlights the urgency for fathers to establish attachment with children experiencing speech delays to ensure optimal development.Keterlambatan bicara pada anak memerlukan parent attachment utuh untuk mengejar ketertinggalan perkembangan. Banyak ayah belum memahami pentingnya peran ini, yang dapat berdampak pada perkembangan sosial, kognitif, keterampilan, dan kepercayaan diri anak. Penelitian ini bertujuan mengeksplorasi dinamika father attachment pada keluarga dengan anak yang mengalami keterlambatan bicara. Menggunakan metode kualitatif pendekatan fenomenologi, penelitian melibatkan empat partisipan ayah dengan anak keterlambatan bicara usia 3-6 tahun. Data dikumpulkan melalui observasi non-partisipan, wawancara semi-terstruktur, dan dokumentasi, lalu dianalisis dengan Interpretative Phenomenological Analysis (IPA). Hasil menunjukkan lima tema induk: kompleksitas keterlambatan bicara, perkembangan anak, paternal involvement, dukungan keluarga, dan paternal deprivation. Temuan dalam penelitian ini mengungkapkan, anak dengan keterlambatan bicara membutuhkan parent attachment utuh. Father attachment dibentuk melalui keterlibatan konsisten yang menekankan komunikasi interpersonal, keterbukaan, dan stimulasi bicara dalam aktivitas sehari-hari. Dukungan keluarga memotivasi ayah membangun kelekatan dengan memenuhi kebutuhan emosional anak. Sebaliknya, paternal deprivation menyebabkan keterasingan anak dan lambatnya perkembangan bahasa serta aspek lainnya. Penelitian ini menekankan urgensi ayah untuk membangun kelekatan dengan anak keterlambatan bicara demi perkembangan optimal.